On the application of approximation of the central manifold of a stationary point to one critical case - Nakonechna, S. O. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We establish conditions under which a central manifold can be replaced by its approximation in the reduction principle for ordinary differential equations in a critical case of one zero root.